Advantages linked to root development enhance rice biomass accumulation under elevated carbon dioxide conditions. (17th August 2020) - He, Jiang; Zhang, Weiyang; Zhu, Kuanyu; Wang, Zhiqin; Wang, Weilu; Yang, Jianchang
Abstract: To explore the effects of an increased CO2 concentration on the growth and N absorption and utilization of different rice ( Oryza sativa L.) cultivars, the Liangyoupeijiu (LY) and Nanjing 9108 (NJ) rice cultivars were grown under ambient CO2 (400 μmol mol −1 ) and elevated CO2 (600 μmol mol −1 ) combined with high N (2.5 mM) and low N (0.5 mM) treatments. The effects of elevated CO2 on root morphological and physiological characteristics, N uptake and utilization, and dry matter accumulation and distribution were analyzed. The results showed that the elevated CO2 levels significantly increased the total biomass of LY under different N levels but only significantly increased the total biomass of NJ under high N. Elevated CO2 significantly increased the N concentrations in the organs of LY but had no significant effect on the N concentrations in the organs of NJ. As a result, elevated CO2 significantly increased the N accumulation of LY but decreased the N uptake of NJ under low N. Under elevated CO2 conditions, the total root length and root surface area of LY increased, and the roots also maintained high activity. The larger roots and higher physiological activity and N accumulation of LY were the important reasons for the high levels of dry matter production in response to elevated CO2 . Improvements in the root morphology and physiological activity of rice in future breeding efforts should enhance the dry matter production of low‐response rice.